The Working towards Sustainability: Study of Banking Sector in Karnataka and Maharashtra (International Journal of Food and Nutritional Sciences, 2022)
Saving the environment during the era of rising global warming has focused on the importance of a better environment for the future. Hence, our research paper aims to “working towards Sustainability in Banking Sector concerning Green Banking In the state of Maharashtra and Karnataka.” Our study on the topic is concerning sustainability with specific reference to digitalization and reducing paperwork to eliminate carbon footprints and reduce pollution. The study to work towrads sustainability is using the Primary data and Secondary data. Where Primary Data is reflecting the respondents using charts and Graph and secondary data is reflecting to charts, Graphs, and websites penetrating in Maharashtra and Karnataka region. This paper attempts to understand the importance of the environment for promoting towards sustainability and to know about customer Awareness and their perception towards the new way of adapting sustainability. This paper has arrived concluded that customers are more focused on the Green Banking system for better sustainable Development.